Soxhlet extraction of oil from candlenut (Aleurites Moluccana): effect of solvent and extraction time - Mahboob, Muhammad Saifullah (2018)
Candlenut oil was extracted using soxhlet extraction technique. The types of solvent and extraction time were optimized using one-factor-at-a-time method. The ground candlenut samples were extracted using ethyl acetate as a solvent. The optimum time for the extraction was found to be 3.5 hours with a highest yield of 72.33%. The highest yield was produced by using ethyl acetate, 72.33%, followed by acetone 46.65%, ethanol 10.1% and the least yield produced by methanol 3.41%. The extracted candlenut oil was analyzed with GC-MS for its chemical constituents were tested with GC-MS analysis and it contains palmitic acid and oleic acid.